Manajemen Kepemimpinan Pendidikan Islam Berbasis Total Quality Management Di Era Disrupsi - Jemani, Abdurahman (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2020)
Leadership is the ability of an individual to influence others or subordinates to work together in order to realize the vision, mission and goals of an organization or educational institution. Leaders have a vital role in moving the wheels of the organization. Therefore, it takes a leader who is capable, technologically literate and able to regulate and manage islamic education organizations or institutions by complying with the principles of the organization being led. This study uses a qualitative approach to the type of library research. Literature research or library research aims to collect data and information sourced from books, scientific articles, magazines, documents, notes, and historical stories as well as other stories contained in the library room. Changes and developments of the times have positive and negative impacts that consciously change human functions and are replaced with technology. Technological changes occur in all joints and fields of life, with no exception islamic educational institutions. This has attracted the attention of stakeholders in the field of islamic education in determining the direction of policy, innovating, developing curriculum and contemporary educational media and changing the pattern of conventional education by synergizing with changes in the current era. Changes - changes in order to improve service quality need to be considered to answer customer demand in this case students and parents of students and be able to print quality output and improve the quality of education at islamic educational institutions.